Room-temperature hydrohydrazination of terminal alkynes catalyzed by saturated abnormal N-heterocyclic carbene-gold(I) complexes - Manzano, Rubén; Wurm, Thomas; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2014)
Abstract A number of saturated abnormal N-heterocyclic carbene (NHC) complexes of gold, in combination with KBArF4 as activator, were successfully applied in the chemoselective addition of hydrazine to alkynes. The reaction proceeds even at room temperature, which was not possible to date with gold catalysts. The reaction can be applied to a number of substituted arylalkynes. With alkylalkynes the yields are low. The saturated abnormal NHC ligands are resistant to isomerization to the saturated normal NHC coordination mode under basic reaction conditions. Under acidic conditions, a simple protonation at the nitrogen atom not neighboring the carbene center was observed and unambiguously characterized by an X-ray crystal-structure analysis. Computational studies confirm that such an isomerization would be highly exothermic, the observed kinetic stability probably results from the need to shift two protons in such a process.
Gesehen am 13.08.2020